2008
DOI: 10.1093/jac/dkn155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antimicrobial therapy on mortality in 377 episodes of Enterobacter spp. bacteraemia

Abstract: Enterobacter spp. are an increasing cause of bacteraemia. The empirical use of piperacillin/tazobactam was independently associated with a lower 30 day mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
5
19
1
Order By: Relevance
“…There were few studies investigating clinical characteristics of bacteremia caused by ESBL-producing E. cloacae though E. cloacae has emerged as a major pathogen causing nosocomial bloodstream infections worldwide in recent years (5,21). A recent report demonstrated the mortality and effects of antibiotic therapy in patients with E. cloacae bacteremia but did not discuss the clinical impact of ESBL production (15). In the present study, compared with bacteremia due to cefotaxime-nonsusceptible E. cloacae isolates without ESBL production, patients in the ESBL group were more likely to have complications of breakthrough bacteremia and a longer hospital stay.…”
Section: Discussioncontrasting
confidence: 66%
“…There were few studies investigating clinical characteristics of bacteremia caused by ESBL-producing E. cloacae though E. cloacae has emerged as a major pathogen causing nosocomial bloodstream infections worldwide in recent years (5,21). A recent report demonstrated the mortality and effects of antibiotic therapy in patients with E. cloacae bacteremia but did not discuss the clinical impact of ESBL production (15). In the present study, compared with bacteremia due to cefotaxime-nonsusceptible E. cloacae isolates without ESBL production, patients in the ESBL group were more likely to have complications of breakthrough bacteremia and a longer hospital stay.…”
Section: Discussioncontrasting
confidence: 66%
“…Our findings are consistent with those of other recent studies (16)(17)(18). A Spanish study spanning a 16-year time period (1991 to 2006) analyzed 377 episodes of Enterobacter spp.…”
Section: Discussionsupporting
confidence: 93%
“…A Spanish study spanning a 16-year time period (1991 to 2006) analyzed 377 episodes of Enterobacter spp. bacteremia and found piperacillin-tazobactam-treated patients had a lower mortality rate than those who received third-generation cephalosporins, carbapenems, ciprofloxacin, or gentamicin (17). However, only 38 patients received piperacillin-tazobactam in this cohort, and for some the treatments were changed to other definitive therapies.…”
Section: Discussionmentioning
confidence: 80%
“…Kaye et al found that PTZ use was not associated with the emergence of cephalosporin resistance in the treatment of Enterobacter bacteraemia (RR = 1.1, 95% CI 0.4-2.7; P = 0.90) [25]. In another study analysing 377 episodes of Enterobacter bacteraemia in adults, the only factor independently associated with a reduction in 30-day mortality was the early use of PTZ [96]. However, another study comparing the risk of isolating a cephalosporin-resistant Enterobacter following PTZ or broad-spectrum cephalosporin therapy showed that both antibiotics conferred the same risk (resistant isolates occurred in 2% for both groups, RR = 1.02; P = 0.95) and that quinolones were protective (RR = 0.24; P = 0.003) [97].…”
Section: Clinical Efficacy Of Piperacillin/tazobactammentioning
confidence: 99%